Selectivity Control in Catalytic Reductive Amination of Furfural to Furfurylamine on Supported Catalysts. Issue 7 (10th March 2020) - Gould, Nicholas S.; Landfield, Harrison; Dinkelacker, Brian; Brady, Casper; Yang, Xuan; Xu, Bingjun
Abstract: Amines are widely used in the manufacture of pharmaceuticals, agricultural chemicals, polymers, and surfactants. However, amines are mostly produced via petrochemical means, which motivates amine production from renewable resources, such as biomass. However, biomass compounds present added challenges involving poor carbon balances. We show that furfural reacts homogeneously with ammonia to produce reactive primary imines, which form large side products and leads to significant carbon losses. The carbon balance is improved by mixing furfural with furfurylamine prior to reaction to form a secondary imine for use as the reaction substrate. While controlling the primary to secondary amine selectivity is a common challenge in reductive amination, supported metal catalysts, including Ni/SiO2, Co/SiO2, and Ru/SiO2 optimize the primary amine yield to 90 to 94 % by using the secondary imine as the reaction substrate. A qualitative correlation between the primary to secondary amine selectivity with the nitrogen binding energy of metals is identified. Abstract : Selectivity control in reductive amination of furfural to the primary amine is challenging. By using the secondary imine derived from furfural and furfuryl amine as the reaction substrate, a net furfuryl amine yield of 90–94 % from furfural is achieved on supported metal catalysts, including Ni/SiO2, Co/SiO2, and Ru/SiO2 .